ผลของความเข้มแสงจากหลอดแอลอีดีต่อการเจริญของยอดอ้อยพันธุ์ขอนแก่น 3 ที่เลี้ยงในระบบไบโอรีแอคเตอร์แบบจมชั่วคราว - ธัญสิริวรรธน์, ธัญญ์วนิช; ปราณีตพลกรัง, เทพพิทักษ์; กาวิชา, ประภาษ; ทัศนัส, ณธกร; คำโฮง, สุมลฑา (Thai Journal of Science and Technology, 2021)
The intensity of light is one of the most important factors for photosynthesis and the developmental processes of plants propagated in the tissue culture systems. The white light from light-emitting diodes (LEDs) and fluorescent lamps was used to compare the effect of different photosynthetic photon flux densities (PPFDs) on the growth of sugarcane cv. Khon Kaen 3 shoots culturing in a temporary immersion bioreactor (TIB). Light treatment composed of six different PPFDs of LED light including 68, 88, 108, 128, 148 and 168 µmol/m2/s, and 68 µmol/m2/s of fluorescent light. The growth parameters, including fresh shoot weight (FW), dry shoot weight (DW), shoot numbers (SN), shoot length (SL), first shoot length (1SL), and shoot cluster diameter (SCD) were recorded. The results showed that the different LED light intensities promoted the sugarcane shoots by increasing FW, DW, SL, and SCD comparable to those subjected to the fluorescent light. The LED light intensity of 128 µmol/m2/s enhanced shoots’ growth by increasing in FW, DW, SN, and SCD. Besides, SL and 1SL of sugarcane shoots were induced by LED light intensity of 68 µmol/m2/s. On the other hand, the FW, SL, and SN decreased with increasing intensity of LED light to 168 µmol/m2/s.